Assessing the global burden of hemorrhage: The global blood supply, deficits, and potential solutions. (November 2021) - Raykar, Nakul P.; Makin, Jennifer; Khajanchi, Monty; Olayo, Bernard; Munoz Valencia, Alejandro; Roy, Nobhojit; Ottolino, Pablo; Zinco, Analia; MacLeod, Jana; Yazer, Mark; Rajgopal, Jayant; Zeng, Bo; et al.
There is a critical shortage of blood available for transfusion in many low- and middle-income countries. The consequences of this scarcity are dire, resulting in uncounted morbidity and mortality from trauma, obstetric hemorrhage, and pediatric anemias, among numerous other conditions. The process of collecting blood from a donor to administering it to a patient involves many facets from donor availability to blood processing to blood delivery. Each step faces particular challenges in low- and middle-income countries. Optimizing existing strategies and introducing new approaches will be imperative to ensure a safe and sufficient blood supply worldwide.